Effects of Different Tree Shapes on Canopy Characteristics of Zaosu Pear (Pyrus ssp. Va.) in the Northwest Arid Zone - Mingxin Zhao; Mingze Ma; Wei Wang; Sufang Cao; Gang Cao; Hongxu Li (Horticulturae)
Zaosu pear (Pyrus ssp. Va., Zaosu) is the main variety of pear cultivated in Gansu Province. Tree shape selection is important in pear cultivation: reasonable tree shapes affect the growth and development of fruit trees and fruit quality, which, in turn, affect the economic benefits of orchards. In this study, Zaosu pear was used as a test material, and five different tree shapes—Y, trunk, single-arm, double-arm, and spindle shapes—were studied regarding three aspects, namely, branching and leafing parameters, light radiation parameters, and root distribution, in order to provide a theoretical basis for the selection of pear tree shapes in arid areas. The results showed that the single-arm and double-arm shapes had the highest fruit weight per fruit values, reaching 280.06 g and 278.27 g, respectively, and the difference in soluble solids—12.42 mg·g−1 and 12.91 mg·g−1, respectively—was not significant; the mu yield of the single-arm shape was 3282 kg; and the yield of a single tree was 39.54 kg, which was the highest for the five tree shapes. The trees mainly had short fruiting branches when they entered the fruiting stage, and the double-arm shape had the highest number of short fruiting branches, which was significantly higher than those of the other tree shapes. Correlation analysis revealed that the number of long fruiting branches was significantly and positively correlated with axillary flower buds. The distribution of light intensity for all five tree shapes showed a gradual increase from bottom to top and from inside to outside, and the single-arm and double-arm shapes had a uniform distribution of light intensity, which translated into better growth and fruiting potential. The trunk shape had the largest leaf area index, resulting in too much depression within the canopy and reducing light, while the single-arm and double-arm shapes had the smallest leaf area indexes, resulting in the light being evenly distributed inside and outside the canopy, and the percentage of light intensity was greater than 50% in all cases, reaching up to 80%. The double-arm form had the highest chlorophyll a content of 24.55 mg·g−1, implying the ability to convert more light energy into chemical energy, and the content of chlorophyll a + b was highest in the single-arm form and the double-arm form, with values of 31.13 mg·g−1 and 33.65 mg·g−1. The total length of the root system and the total surface area of the root system for the single-arm shape were the largest, i.e., 558,550.64 cm and 79,252.32 cm2, respectively, indicating that it has stronger adaptability and resource acquisition ability compared to the other tree shapes. In conclusion, the single-arm form is more suitable for planting in arid areas.